The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.appet.2006.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against memorial facilitation and context-dependent memory effects through the chewing of gum

Abstract: The experiment examined the prediction that chewing gum at learning and/or recall facilitated subsequent word recall. Chewing gum at learning significantly impaired recall, indicating that the chewing of gum has a detrimental impact upon initial word encoding. In addition, a context-dependent memory effect was reported for those participants who both learned and recalled in the absence of gum, however a context dependent effect was not found with chewing gum. The findings contradict previous research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 10 publications
2
27
1
Order By: Relevance
“…The interaction demonstrates that both context‐change combinations resulted in poorer recall than both context‐same combinations. This finding is novel with respect to previous studies (e.g., Johnson & Miles, 2007, 2008; Miles & Johnson, 2007, 2010) in which the context‐change combinations did not result in poorer recall compared to the context‐consistent combinations.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…The interaction demonstrates that both context‐change combinations resulted in poorer recall than both context‐same combinations. This finding is novel with respect to previous studies (e.g., Johnson & Miles, 2007, 2008; Miles & Johnson, 2007, 2010) in which the context‐change combinations did not result in poorer recall compared to the context‐consistent combinations.…”
Section: Discussioncontrasting
confidence: 62%
“…The observed CDM effect in the present study is curious with respect to past null effects for those studies in which context has been manipulated via the presence or absence of chewing a single gum pellet (e.g., Johnson & Miles, 2007, 2008; Miles & Johnson, 2007, 2010). Intuitively, gum chewing compared to non‐gum chewing appears contextually more distinct than chewing one gum pellet compared to four gum pellets.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Johnson and Miles 6 found that significantly more words were recalled in the no-gum learning condition. No context-dependent effect was present in the gum condition even though it was involved in the no-gum condition (i.e.…”
Section: Introductionmentioning
confidence: 96%